The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1603/0022-2585-39.6.926
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Field Observations on Duration of Gonotrophic Cycle of <I>Anopheles albitarsis</I> s.l. (Diptera: Culicidae) in Southeastern Brazil

Abstract: Mark-release-recapture experiments were conducted to determine the duration of the gonotrophic cycle of Anopheles albitarsis s.l. in Ribeira Valley, State of Sao Paulo, Brazil. Separate experiments with females collected from the field were followed under laboratory conditions. A mean of 2.4 d was characteristic for the gonotrophic cycle for wild-caught females, whereas 4.4 d was characteristic for females in the laboratory conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…in which the gonotrophic cycle was estimated from egg development were sufficiently different from the field conditions in which the feeding cycle was measured to explain the difference between the estimates of the gonotrophic and feeding cycles. A similar study for Anopheles albitarsis in Brazil [ 37 ], also found a longer gonotrophic cycle (calculated from oviposition observations) than the feeding cycle (from mark-release-recapture experiments).…”
Section: Discussionmentioning
confidence: 65%
“…in which the gonotrophic cycle was estimated from egg development were sufficiently different from the field conditions in which the feeding cycle was measured to explain the difference between the estimates of the gonotrophic and feeding cycles. A similar study for Anopheles albitarsis in Brazil [ 37 ], also found a longer gonotrophic cycle (calculated from oviposition observations) than the feeding cycle (from mark-release-recapture experiments).…”
Section: Discussionmentioning
confidence: 65%
“…had gonotrophic cycles of 6–7 days. This is a highly unlikely scenario, since the variation in the literature has ranged from 2.3 to 4.4 days for this species, with different sampling methods [7] and the longest reported Nyssorhyncus cycle is 5 days [39].…”
Section: Discussionmentioning
confidence: 99%
“…darlingi . An average value of 2.3 days was obtained under field conditions in Brazil [25], but the gonotrophic cycle duration can vary from 2.4 to 4.4 days for the same species and from 2 to 5 days for Nyssorhynchus species [26]. Unpublished laboratory observations showed that the gonotrophic cycle of An.…”
Section: Methodsmentioning
confidence: 99%